Serum brain natriuretic peptide in preeclamptic patients and normotensive pregnant women - Reyna Villasmil, Eduardo (2017)
Objective: To compare serum brain natriuretic peptide concentrations in preeclamptic patients and healthy normotensive pregnant women. Design: Case-control study. Setting: Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: A total of 180 patients were selected. Ninety preeclamptic patients were selected as the study group (group A) and 90 healthy normotensive pregnant women with the same age and body mass index as the study group were selected as controls (group B). Methods: Blood samples were extracted from all patients before labor and immediately after diagnosis in group A to determine serum cerebral natriuretic peptide concentrations. Main outcome results: General characteristics, serum brain natriuretic peptide concentrations and diagnostic efficacy. Results: There was a statistically significant difference in serum brain natriuretic peptide concentrations between group A (65.1 +/- 14.1 pg/mL) and group B (43.2 +/- 9.8 pg/mL; p < 0.001). There was no significant correlation with systolic and diastolic blood pressure values (p = ns). A cutoff value of 55 pg/mL had an area under the curve of 0.88, sensitivity 71.1%, specificity 83.3%, positive predictive value 81.0% and negative predictive value 74.2%, with diagnostic accuracy of 77.2%. Conclusion: Preeclamptic patients have s ignificantly h igher concentrations of serum brain natriuretic peptide compared to healthy normotensive pregnant women. Objective: To compare serum brain natriuretic peptide concentrations in preeclamptic patients and healthy normotensive pregnant women. Design: Case-control study. Setting: Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: A total of 180 patients were selected. Ninety preeclamptic patients were selected as the study group (group A) and 90 healthy normotensive pregnant women with the same age and body mass index as the study group were selected as controls (group B). Methods: Blood samples were extracted from all patients before labor and immediately after diagnosis in group A to determine serum cerebral natriuretic peptide concentrations. Main outcome results: General characteristics, serum brain natriuretic peptide concentrations and diagnostic efficacy. Results: There was a statistically significant difference in serum brain natriuretic peptide concentrations between group A (65.1 +/- 14.1 pg/mL) and group B (43.2 +/- 9.8 pg/mL; p < 0.001). There was no significant correlation with systolic and diastolic blood pressure values (p = ns). A cutoff value of 55 pg/mL had an area under the curve of 0.88, sensitivity 71.1%, specificity 83.3%, positive predictive value 81.0% and negative predictive value 74.2%, with diagnostic accuracy of 77.2%. Conclusion: Preeclamptic patients have significantly higher concentrations of serum brain natriuretic peptide compared to healthy normotensive pregnant women.